2017
DOI: 10.1177/0886260517709801
|View full text |Cite
|
Sign up to set email alerts
|

When the Cop Is the Victim: A Test of Target Congruence Theory on Intimate Partner Violence Victimization Experienced by Police Officers

Abstract: This study analyzed data from the Police Stress and Domestic Violence in Police Families in Baltimore, Maryland, 1997-1999 ( N = 753) to examine propositions derived from target congruence theory in the context of intimate partner violence (IPV) victimization experienced by police officers. Specifically, this study tested the influence of target vulnerability, target gratifiability, and target antagonism on IPV victimization. Results from logistic regression models showed that all three theoretical constructs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…Although tests of the theory are few, target congruence has found support as a theory of personal victimization (e.g., Finkelhor & Asdigian, 1996; O & Wilcox, 2017; Sween & Reyns, 2017; Waldner & Berg, 2008; Zavala, 2017). For example, Finkelhor and Asdigian (1996) found that variables representing all three of the core concepts—such as psychological distress (vulnerability) and risky behavior (antagonism)—predicted youth victimization (Finkelhor & Asdigian, 1996).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tests of the theory are few, target congruence has found support as a theory of personal victimization (e.g., Finkelhor & Asdigian, 1996; O & Wilcox, 2017; Sween & Reyns, 2017; Waldner & Berg, 2008; Zavala, 2017). For example, Finkelhor and Asdigian (1996) found that variables representing all three of the core concepts—such as psychological distress (vulnerability) and risky behavior (antagonism)—predicted youth victimization (Finkelhor & Asdigian, 1996).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Despite its applicability to personal forms of victimization, target congruence theory has not been extensively tested. Indeed, it has been applied to only a handful of types of victimization (e.g., antigay violence, intimate partner violence, sexual victimization, youth victimization), but with promising results (Elvey, 2016; Finkelhor & Asdigian, 1996; Sween & Reyns, 2017; Waldner & Berg, 2008; Zavala, 2017). To date, no research has tested the theory as an explanation for stalking victimization.…”
Section: Introductionmentioning
confidence: 99%
“…The current study will examine the respondent's level of anger and immigration status, all of which can reasonably ignite anger, jealousy, and other adverse impulses from the perpetrator. For instance, in regard to anger, there is the possibility that a person's angry outburst can arouse the anger of the offender, leading to the likelihood of victimization (see, Zavala, 2017). Similarly, a Latina may be personally victimized on the grounds of their immigration status as in the form of a hate crime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Creating a combined victimization variable with physical violence, stalking, and threats is potentially problematic because these distinct and separate incidents may have different, unique covariates. The majority of research testing target congruence theory use physical victimization as their dependent variable Finkelhor & Asdigian, 1996;Sween & Reyns, 2017;Zavala, 2017). 5.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
See 1 more Smart Citation